Sensitivity analysis of heat flow of heat exchangers in ethanol-water distillation column - Kállai, Viktória; Szepesi L., Gábor (Multidiszciplinaris Tudomanyok, 2023)
In this study sensitivity analysis was made with Unisim Design process simulator software for ethanol-water mixture.  The effect of the reflux ratio and the number of trays on the heat flow of the heat exchangers was investigated in case of different purification of bottom product. The results of the sensitivity analysis showed that the heat flow of the reboiler averagely 1.94 times higher than the heat flow of the condenser. Afterwards, the effect of the thermal state of the feed stream was investigated on the heat flow of the condenser and the reboiler. In each cases the mass flow and ethanol content of the distillate stream were also investigated. The results showed that in the studied cases the liquid volume percent of the ethanol varies between 65% and 87%. A simplified cost estimation was calculated with the determination of mass flow of cooling water and low-pressure steam. From the results it was concluded that higher number of trays, higher temperature of the feed stream and higher ethanol content in the bottom product resulted lower costs of the utility streams.